Several Tsunami Scenarios at the North Sea and their consequences at the German Bight - Chacon-Barrantes, Silvia (2013)
Tsunamis occurred in the past at the North Sea, but not frequently. There are historical and geological records of several tsunamis: the Storegga tsunami caused sediment deposits in Scotland 8,000 years ago and records of at least six earthquake-generated tsunamis exist from 842 to 1761 AC. The highest tsunami height witnessed at the German Bight is comparable to the maximum storm surge recorded and could thus cause similar or higher damage. However, there is little research on tsunami modeling in the North Sea. Here, we performed ten numerical experiments imposing N-waves at the open boundaries of a North Sea model system to study the potential consequences of tsunamis for the German Bight. One of the experiments simulated the second Storegga slide tsunami, seven more explored the influence of the incidence direction of the tsunami when entering the North Sea domain, and the other two explored the influence of tides on tsunami heights. We found that the German Bight is not exempt from tsunami risk. The main impact was from waves entering the North Sea from the north, even for tsunamis with sources south of the North Sea. Waves entering from the English Channel were attenuated after crossing the Dover strait. For some scenarios, the tsunami energy got focused directly at the Frisian Islands. The tidal phase had a strong influence on tsunami heights, although in this study the highest heights were obtained in the absence of tides. The duration of tsunamis is significantly smaller than that of storm surges, even though their flow velocities were found to be comparable or larger, thus increasing their possible damage. Therefore, tsunamis should not be dismissed as a threat at the North Sea basin and particularly at the German Bight.